Deep brain stimulation for trigeminal autonomic cephalalgias - Messina, Giuseppe; Broggi, Giovanni; Levi, Vincenzo; Franzini, Angelo (Expert review of neurotherapeutics, 2018)
: Deep brain stimulation (DBS) of the posterior hypothalamic region (pHyr) has been shown to be efficacious for more than a half of patients suffering from trigeminal autonomic cephalalgias (TACs); nonetheless, controversies about the mechanisms of action and the actual site of stimulation have arisen in recent years. : Firstly, a review of the most recent literature on the subject is presented, stressing the critical points that could, in the future, make a difference for optimal management of patients afflicted by these life-threating diseases. Hypothalamic functional anatomy, experimental data and pathophysiological hypotheses are reported. : About 32% of patients who underwent DBS for TACs are pain-free. The determination of the pHyr region seems to be crucial for the generation of pain attack in these pathologies, although other structures are involved in complex mechanisms and circuits that interact with each other. Neurophysiological data, combined with more advanced experimental models, are of primary importance regarding our understanding of what the real target is, and how to overcome the issue of refractory patients.